ANALYSIS OF CARBON STOCK IN SEAGRASS Cymodocea rotundata IN TUAPEJAT WATERS, MENTAWAI ISLAND DISTRICT - Oktari, Mela; Amin, Bintal; Efriyeldi, Efriyeldi (Asian Journal of Aquatic Sciences, 2023)
This research was conducted in January 2022. Seagrass density calculations and seagrass sampling were carried out in Dusun Jati, Tuapejat, Sipora Utara District, Mentawai Islands Regency, and seagrass sample analysis was carried out at the Marine Chemistry Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The objective of the study is to analyze the density of seagrass C. rotundata, analyze the biomass and carbon stock stored in Agb and Bgb parts, and whether there are differences in density, biomass, and carbon stock between stations in seagrass C. rotundata at the research site. The density value of seagrass C.rotundata varies for each station. The average density of seagrass C. rotundata at the study site was 33.48 stands/m2. The range of the biomass value in the Agb section is 21.78-39.9 gbk/m2 while the Bgb section is 31.01-61.4 gbk/m2. The average value of the carbon stock stored in the Agb section is around 2.08-5.34 gC/m2 and the Bgb section is 10.81-15.48 gC/m2. The conclusion from this research is that the density of seagrass at the research location is infrequently and each station has a different density. The highest biomass is found at a greater density as well as the carbon stock. Biomass between stations was not significantly different while the Agb and Bgb parts were significantly different. Density, biomass, and carbon stock have a very strong relationship.